Mode and Dimension of Facilitation in Student-Centred Learning Approach: A Comparison of Teaching Experience - Masek, Alias (International Journal of Active Learning, 2019)
This study is based on the Heron Facilitation Model, to evaluate the dimension and mode of facilitation of facilitators who are using Student-Centred Learning (SCL) as an approach in delivering theoretical knowledge. A survey study was conducted, involving 177 facilitators from multiple backgrounds. The findings show that the six dimensions of facilitation were rated at a high level and cooperative mode was most often applied in the SCL approach. There is no difference in mode and dimension applied by young and senior facilitators. Thus, experience and field of education discipline do not generally predict an effective facilitation measure for theoretical delivery.